(untitled) (Economics and region, 2018)
Globalization is the leading trend of the modern economic system. The states’ transformation into a single global structure takes place under its influence. Globalization affects all areas of public life, changes stereotypes and values. The aim of the article is to study the process of economic globalization and analyze its main consequences and contradictions. In the article the authors study the main features of economic globalization. It is dedicated main sources of the globalization process, namely technological progress and trade liberalization. Separately it is analyzed the subjects of the globalization, such as post-industrial states and multinational corporations. The authors highlight the factors, which promote the process of economic globalization. It is emphasized that the process has a different impact on the world economy and also has both positive and negative consequences. Globalization divides the world into two camps: the countries that will benefit from this process and countries that lose. And the less a country is developed, the less it will benefit from globalization. In countries, which have adapted to it, stability and prosperity are increasing. So despite the fact that globalization reinforces cooperation between countries, it promotes the growth of the uneven development. This is the basic contradiction of globalization. Thus, globalization is an objective process, but each country should strive to reduce the negative effects of globalization process and getting the most benefit from it.